Pengaruh Likuiditas, Profitabilitas, Solvabilitas Dan Operating Cash Flow Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2021-2024 - Aditya Rengga Mahesa; Eviana Lailatul Safitri (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
This research was conducted to understand the influence of liquidity, profitability, solvency, and the Operating Cash Flow Ratio on profit growth in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study employed an associative quantitative methodology, utilizing purposive sampling for data selection. Twenty companies met the research criteria, resulting in a total of 80 observations. Multiple linear regression analysis was used, with data processed via SPSS version 26. The findings indicate that liquidity (proxied by the Current Ratio/CR), solvency (proxied by the Debt to Equity Ratio/DER), and the Operating Cash Flow Ratio (OCFR) have a positive and significant effect on profit growth. Conversely, profitability (proxied by Return on Assets/ROA) has a negative and significant effect on profit growth. The results demonstrate that a company's ability to manage liquidity, capital structure, and operating cash flows plays a crucial role in driving profit growth for mining sector companies.